2002
DOI: 10.1002/1521-4141(200212)32:12<3776::aid-immu3776>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of type?II collagen is of major importance for T cell tolerance and pathology in collagen-induced arthritis

Abstract: Type II collagen (CII) is a candidate cartilage‐specific autoantigen, which can become post‐translationally modified by hydroxylation and glycosylation. T cell recognition of CII is essential for the development of murine collagen‐induced arthritis (CIA) and also occurs in rheumatoid arthritis (RA). The common denominator of murine CIA and human RA is the presentation of an immunodominant CII‐derived glycosylated peptide on murine Aq and human DR4 molecules, respectively. To investigate the importance of T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 24 publications
3
59
0
Order By: Relevance
“…This results in smaller CII fragments being picked up by APC and presented by MHC class II. Previous studies from our laboratory showed that CII-specific T cells predominantly recognize glycosylation at position 264 in the CII260-270 epitope and that glycosylated CII is more arthritogenic than non-glycosylated CII is [3,11,13,20]. In addition, adoptive transfer of glycopeptidespecific T cells into CII-immunized DBA/1 mice increases the incidence and severity of arthritis as well as the production of CII-specific antibodies [21].…”
Section: Discussionmentioning
confidence: 84%
“…This results in smaller CII fragments being picked up by APC and presented by MHC class II. Previous studies from our laboratory showed that CII-specific T cells predominantly recognize glycosylation at position 264 in the CII260-270 epitope and that glycosylated CII is more arthritogenic than non-glycosylated CII is [3,11,13,20]. In addition, adoptive transfer of glycopeptidespecific T cells into CII-immunized DBA/1 mice increases the incidence and severity of arthritis as well as the production of CII-specific antibodies [21].…”
Section: Discussionmentioning
confidence: 84%
“…In two subsequent reports, Holmdahl's group demonstrated that protection from collagen-induced arthritis in animals could be afforded by treatment with galactosylated CII peptide and that this epitope is the immunodominant form in RA patients because of incomplete tolerance [21,22]. These data suggest a specific role for adaptive T cell recognition of glycosylated antigens in arthritis disease progression.…”
Section: Glycosylation and Diseasementioning
confidence: 98%
“…It was evident that the carbohydrate contents of collagen isolated from commercial shark cartilage capsules were between 5 and 40 % (Merly and Smith 2013). Backlund et al (2002) opined that glycoprotein content of CII is a key element for the recognition of T cell in collagen-induced arthritis models. Recently, Merly and Smith (2013) studied the effect of oral administration of fetal bovine articular cartilage collagen for the treatment of RA.…”
Section: Glycoprotein/carbohydrate Contentmentioning
confidence: 99%